EL ROL EDUCATIVO DEL MUSEO DIDÁCTICO PALEONTOLÓGICO DE OCUCAJE, ICA, PERU - Villaseca, Andrea (2020)
The Paleontological Didactic Museum of Ocucaje (PDMO) is located in Ocucaje, Ica, Perú. It was founded in 2015, under the management of the District Municipality since that day it has received countless visits from tourists, families, schools and universities. The aim of this work is to communicate to general public, students, scientists, teachers, and professors the distribution of rooms and educational materials (illustrations, models, dioramas) of the Paleontological Didactic Museum of Ocucaje (PDMO). Nowadays, it has five exhibition halls, one library, 26 models representing peruvian species like Cinthyacetus peruvianus Martínez-Cáceres & Muizon, 2011 (Cetacea, Basilosauridae), Ocucajea picklingi Uhen et al., 2011 (Cetacea, Basilosauridae), Livyatan melvillei Lambert et al., 2010 (Cetacea, Physeteroidea) y Odobenoceptos peruvianus Muizon, 1993 (Cetacea, Odobenocetopsidae); extinct animals autochthonous of Ocucaje, three dioramas, 22 illustrations of the reconstruction of native fossils, one school project and one public exhibition. Undergraduate students of Ricardo Palma University, the National University of Arequipa and the National Agrarian University of La Molina visited the museum with undergraduate students.  Quarterly visits were carried out over 4 years in order to describe the current state of the PDMO and describe  teaching material, also for prepare a detailed list and propose educational activities. It is concluded that the Ocucaje Paleontological Museum is developed as a continuous learning space and students are part of it in a dynamic way acquiring new scientific knowledge.